A systematic – Review of academic stress intended to improve the educational journey of learners - Iqra (Methods in Psychology)
As learners progress through their educational path, they experience various hassles and transitions, certainly encountering stress along the way. This can be due to the academic burdens placed on them, the personal growth they endure, and the adjustments required in new settings, all fundamental to their educational experiences. Preeminent academic stress is a concerning problem worldwide, affecting every facet of students’ lives. Hence, it is crucial to have a full understanding of academic stress, including its sources, symptoms, and ramifications, in order to recommend appropriate intervention strategies. Previously, many review articles have been published covering various aspects of academic stress, but this review aims to serve as an umbrella term for academic stress, enclosing every aspect under its thorough coverage. Data is collected from various journals using different virtual databases, primarily Google Scholar. The search was done using keywords relevant to every phase of academic stress such as academic stress, causes of stress among students, impacts of stress, symptoms of stress, management techniques, etc. The review comprehensively explores stress at academic levels, covering causes, symptoms, detection tools, and impacts, and proposing effective coping tactics beneficial for students to cope with stress.